To the Question of Organizing the Career Guidence in Artisan Occupations - A. V. Yefanov; Y. A. Nemtchinova (Russian State Vocational Pedagogical University, 2015)
The paper looks at the institutional and functional features of the artisan activities, and vocational training of future artisans- entrepreneurs; the specificity of career guidance in related training profiles is discussed. In the course of successful socio-economic development, the given specialists can form a considerable part of the Russian middle class strata. However, there exist the two opposite trends: on the one hand, the specialists realize the modern day requirements for vocational training and enrollee selection, while, on the other hand, the majority of the society regards the artisan occupations as common and primitive. This controversy signals the urgent need for vocational guidance addressed to the school leavers. The authors suggest using acmeology - the studies of the highest professional achievements - along with psychological facilitation and visual grounds for career guidance development. The paper is recommended to the secondary school teachers, vocational training teachers and sociologists analyzing and predicting the labor market demands.